Conjunctival squamous cell carcinoma with massive apoptosis and immune cell infiltration: A case report - Du, Gang; Qiao, Jun; Lei, Xunwen; Han, Ruiqin (Frontiers in Surgery, 2022)
This case reports a rare case of conjunctival squamous cell carcinoma in Chinese. The elderly (86-year-old) female patient was diagnosed and treated effectively after three times of diagnosis. During this period, she was misdiagnosed and ineffective treatment for many times. Therefore, we propose to make an integrated diagnosis based on histopathological diagnosis, combined with a variety of diagnostic methods including MRI and CDFI, supplemented by updated multiple immunohistochemically techniques, so as to achieve the purpose of accurate diagnosis.